Nanoscale Optoregulation of Neural Stem Cell Differentiation by Intracellular Alteration of Redox Balance. (11th August 2017) - Hassanpour‐Tamrin, Sara; Taheri, Hossein; Mahdi Hasani‐Sadrabadi, Mohammad; Hamed Shams Mousavi, S.; Dashtimoghadam, Erfan; Tondar, Mahdi; Adibi, Ali; Moshaverinia, Alireza; Sanati Nezhad, Amir; Jacob, Karl I.
Abstract : Regulation of stem cell (SC) fate, a decision between self‐renewal and differentiation, is of immense importance in regenerative medicine and has been proven to be a powerful stimulus regulating many cell functions influencing the SC fate. This study uses triphenylphosphonium‐functionalized gold nanoparticles (TPP‐AuNPs) to explore the interplay of intracellular electromagnetic (EM) exposure and the SC fate. Localized EM waves are generated inside neural stem cells (NSCs) to stimulate TPP‐AuNPs (AuNPs), targeting the mitochondria through inducing reactive oxygen species and differentiating these cells into neurons. Following laser irradiation of TPP‐AuNPs‐transfected NSCs, their differentiation to neurons is monitored by tracing the relevant markers both at the genetic and protein levels. The electrophysiology technique is further used to examine the functionality of neurons. The results confirm that TPP‐AuNPs subjected to electromotive forces have the potential to regulate cellular fate, although further investigations are still required to shed light on the mechanisms underlying the interaction of EM‐stimulated TPP‐AuNPs on cellular fate to design highly adjustable cell differentiation and reprogramming methods. Abstract : Regulation of stem cell fate is a decision between self‐renewal and differentiation, and it can be altered remotely. Here, functionalized gold nanoparticles are used to generate localized electromagnetic fields inside neural stem cells to stimulate their neural differentiation by inducing reactive oxygen species near the mitochondria.